Epidemiological Trends of Dengue Fever among Children of Gandaki Province - Bagale, Bishow Bandhu; Bhandari, Anita (Journal of Bharatpur Hospital, 2025)
Background Dengue fever is an emerging public health concern in Nepal, with rising incidence and frequent outbreaks. In Gandaki Province, it affects all age groups, including children who are particularly vulnerable to severe forms. This study aims to assess the demographic patterns, geographical distribution, seasonal variation, and temporal trends of dengue among children in Gandaki Province, Nepal. Methods This study analyzed secondary surveillance data from the Early Warning and Reporting System (EWARS) and District Health Information System 2 (DHIS2) from January 2021 to December 2024. Laboratory-confirmed dengue cases among children aged 0–14 years were included. Descriptive statistics summarize demographics, while temporal, seasonal, and district-level analyze identified trends and geographical clustering. Results A total of 7,412 dengue cases were reported among children during the study period, increasing from 233 in 2021 to 3,508 in 2024. Males accounted for 60.2% (4,461) and females 39.8% (2,951), with a male-to-female ratio of 1.5:1. The highest burden occurred in Kaski district, followed by Tanahun and Gorkha, while Manang reported the fewest cases. A distinct seasonal peak was observed in September (1,324 cases) and October (1,278 cases) following the monsoon. Conclusions Dengue fever among children in Gandaki Province showed a steady increase over four years, with geographical clustering in high burden areas with peaks during September and October. These findings highlight sociocultural, environmental and geographical influence on transmission of dengue among children of Gandaki Province.